Hepatitis B Surface Antibody (HBsAb) Screening with Rapid Test among Teenagers in Surabaya - Moch Irfan Hadi; Muhammad Yusuf Alamudi (Journal of Health Science and Prevention, 2017)
Hepatitis was an inflammation or infection of the liver cells and generally caused by the virus, resulting in the liver swelled. Hepatitis B disease is caused by acute or chronic Hepatitis B virus and includes the most dangerous liver disease. World Health Organization (WHO) estimates in 2002 that one billion living individuals are infected with Hepatitis B, so more than 200 million people worldwide are infected, and 1-2 million deaths annually are associated with VHB. In 2008 the number of people infected with VHB was 2 billion, and 350 million people continued to be patients with chronic hepatitis B infection. Generally most of Hepatitis B immunization studies that have been conducted in Indonesia only observe the early age group (infant) and quite rare for adolescence groups. Those group of teenagers becomes very important subject because they will soon be married and have children in the future. The research aimed to investigated HbsAb-based hepatitis using Rapid test among teenagers. This research was conducted in the Boarding School Health Study Center of Nadhlatul Ulama University Surabaya. Fifty-four teenagers were tested using HbsAb rapid test. The HBsAb rapid test result found 2 teenagers positive to hepatitis.